The cost of integrated HIV care and buprenorphine/naloxone treatment: results of a cross-site evaluation. - Schackman, Bruce R; Leff, Jared A; Botsko, Michael; Fiellin, David A; Altice, Fredrick L; Korthuis, P Todd; Sohler, Nancy; Weiss, Linda; Egan, James E; Netherland, Julie; Gass, Jonathan; Finkelstein, Ruth (Journal of acquired immune deficiency syndromes (1999), 2011)
Implementing integrated HIV and buprenorphine/naloxone treatment requires cost estimates to plan and obtain funding.
Keywords: Anti-HIV Agents; Buprenorphine; Delivery of Health Care, Integrated; Health Care Costs; HIV Infections; Humans; Naloxone; Narcotic Antagonists; Opioid-Related Disorders